New record of Pantophthalmus pictus (Wiedemann, 1821) (Diptera, Pantophthalmidae) in the Cerrado vegetation of central Brazil - Pujol-Luz, José Roberto; Morgado, Giovanna Souto (Papéis Avulsos de Zoologia, 2018)
Pantophthalmus pictus (Wiedemann, 1821) (Diptera, Pantophthalmidae) has been reported to occur in south and southeastern Brazil, Paraguay and Argentina. Here we report the first occurrence of these rare flies in the Cerrado vegetation of central Brazil. We also provide an updated list of the geographical distribution of the 20 species of the genus Opetiops Enderlein, 1921 (1 species) and Pantophthalmus Thunberg, 1919 (19 species) in the Neotropical region.